Stress Level Relationship with Prediabetes Events in Sleman Yogyakarta - Novi Husmarini; Wahyudi Istiono; Ronny Tri Wirasto (Faculty of Medicine, Public Health, and Nursing, 2019)
BACKGROUND: Prediabetes prevalence in the world is increasing, and is estimated to reach20.6% in 2025. Prediabetes prevalence in Indonesia is almost double the prevalence of diabetes mellitus. Prediabetes often does not cause symptoms, but has already started to occur with both microvascular and macrovascular complications in some patients. Stress is a disorder of the body and mind caused by changes and demands of life. Stress that occurs at this time, is part of the effects of modern life, and cannot be avoided, both in the work environment, and school, as well as family and society. In the state of stress the secretion of the hormone cortisol increases, which pushes the pancreas to produce insulin, so that there is an increase in blood sugar levels.OBJECTIVE: This study was conducted with the aim to know the relationship of stress level in prediabetes sufferer and know the description of stress level of prediabetes patient in Sleman Yogyakarta area.METHODS: This research was a quantitative studywith a cross sectional design, done in the working area of first health facility of Sleman Regency, Yogyakarta. Sampling was done by simple random sampling, and research subjects were patients in the working area of Puskemas in Sleman that fulfilled inclusion and exclusion criteria then examined.RESULTS: The mean age of the study subjects was 46.7 years (SD 11.02). The distribution of subjects of the study was 121 females (78.1%), and 34 males (21.9%). Based on a total of 155 respondents, 19 respondents (12.3%) were diagnosed with prediabetes based on TTGO results and 136 people (87.7%) had normal TTGO results. Based on a total of 155 respondents, 69 respondents (47.1%) had a mild stress level, 80 respondents (49%) moderate stress level and 6 respondents (3.9%) had severe stress level. The result of bivariate analysis showed that there was no correlation between stress level and prediabetes occurrence in Sleman Yogyakarta and p = 0.825 (CI 95%: 0.879-1.67) was not statistically significant (p>0.05). Prediabetes prevalence was 12.3% in the study population.CONCLUSSION: There was no correlationbetweenstress level with the occurrence of prediabetes in Sleman Yogyakarta area. Stress levels were moderate among prediabetes sufferers more than mild and severe stress levels.